2019
DOI: 10.3390/bs10010017
|View full text |Cite
|
Sign up to set email alerts
|

EEG “Signs” of Verbal Creative Task Fulfillment with and without Overcoming Self-Induced Stereotypes

Abstract: The study aimed to reveal task-related differences in story creation with and without the mental effort of overcoming self-induced stereotypes. Eighteen right-handed subjects (19.3 ± 1.1 years old) created stories. The subjects reported the formation of story plot stereotypes (as we call them: self-induced) during self-regulated creative production, which had to be overcome with the instruction to continue the story. Creative task fulfillment (without formed stereotypes-first stage of creation) was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In addition, this finding is consistent with that alpha power desynchronization being associated with the generation of first responses of four alternative uses 27 . Similarly, alpha power desynchronization was also observed during the verbal creative tasks fulfillment with and without overcoming self-inducted stereotypes, which lasted a few minutes 84 . Moreover, alpha power decreased significantly over temporal sites during evaluation compared to during idea evolution.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, this finding is consistent with that alpha power desynchronization being associated with the generation of first responses of four alternative uses 27 . Similarly, alpha power desynchronization was also observed during the verbal creative tasks fulfillment with and without overcoming self-inducted stereotypes, which lasted a few minutes 84 . Moreover, alpha power decreased significantly over temporal sites during evaluation compared to during idea evolution.…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies in the field of neurocognitive creativity demonstrated the functional role of changes in alpha power. Some studies indicated that alpha power decreased from rest to creativity-related tasks 17 , 19 , 68 , 76 while others reported that alpha power increased from rest to creativity related tasks following a U-shaped curve 77 80 . The former is in line with the finding that a reduction of alpha power is associated with a more complex and ill-defined problem, especially in ecologically valid settings where a higher cognitive workload is triggered 17 , 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Idea generation is related to activity in the default-mode network (DMN) while idea evaluation is linked to the executive control network 10 13 . EEG studies indicated that idea generation is associated with decreases in alpha power over almost all sites, suggesting increased cognitive workload 14 19 . An increase in cognitive workload frequently occurs at the beginning and end of idea generation 20 , 21 , an effect that influences the subjective rating of task difficulty 22 .…”
Section: Introductionmentioning
confidence: 99%